Orofacial manifestation of hematological disorders: Hemato-oncologic and immuno-deficiency disorders - Titilope A Adeyemo; Wasiu L Adeyemo; Adewumi Adediran; Abd Jaleel A Akinbami; Alani S Akanmu (Wolters Kluwer Medknow Publications, 2011)
The aim of this paper is to review the literature and identify orofacial manifestations of hematological diseases with special reference to hemato-oncologic, immuno-deficiency disorders, and human immunodeficiency virus infection. A computerized literature search using MEDLINE was conducted for published articles on orofacial manifestations of hematological diseases with emphasis on hemato-oncologic and human immunodeficiency virus (HIV) infection. Mesh phrases used in the search were: Oral diseases AND hematological disorders; orofacial diseases AND leukemias; orofacial lesions AND lymphomas; orofacial diseases AND multiple myeloma, orofacial manifestations AND HIV. The Boolean operator "AND" was used to combine and narrow the searches. The full texts of these articles were thoroughly examined. References in these articles also were manually searched non-Medline articles. Only relevant articles were selected for the review. Orofacial manifestation of malignant hematological diseases may present as primary clinical features due to infiltration of orofacial tissues, or as secondary due to the subsequent infiltration of normal bone marrow elements, or tertiary due to the side effects of the treatment. HIV-associated orofacial lesion may be a clinical indicator of HIV infection in otherwise healthy, undiagnosed individuals; an early clinical feature of HIV infection; clinical markers for the classification and staging of HIV disease or may be a predictor of HIV disease progression. Orofacial manifestations of malignant hematological diseases and HIV infection are not uncommon findings in clinical practice. These manifestations may be clinical indicators of hematologic disorders in otherwise healthy, undiagnosed individuals.